Suitcase security system using Android and GPS - Hendri, Hendri; Rosyinta, Rosyinta (Jurnal Pendidikan Teknologi Kejuruan, 2022)
Technological progress is something that cannot be avoided in line with the development of science. Technology provides many benefits because technology is present to facilitate human work. One of the technological advances is the presence of airplanes. To go wherever humans are not restricted by distance and time. Generally, people will use a suitcase to store their luggage when they travel because it is easier to carry. But the theft of items in the suitcase is rampant. For this reason, a security system can be made that can inform the owner that the suitcase has been forcibly opened. The PIR sensor installed in the suitcase will detect if there is movement and temperature of the human body heat in the suitcase. Then GSM SIM900A will send a notification to the owner and the buzzer will sound. If the suitcase has been stolen and taken away then we can see the location of the suitcase in the application that has been made with coordinates obtained from the GPS module installed in the suitcase. In addition, we can activate or deactivate the sensor through an application that has been made with the aim that when the owner opens the suitcase there will be no notification that the suitcase has been forced open and the buzzer will not ring.